Design and Synthesis of Iminosydnones for Fast Click and Release Reactions with Cycloalkynes. Issue 34 (17th May 2018) - Riomet, Margaux; Decuypere, Elodie; Porte, Karine; Bernard, Sabrina; Plougastel, Lucie; Kolodych, Sergii; Audisio, Davide; Taran, Frédéric
Abstract: Emerging applications in the field of chemical biology are currently limited by the lack of bioorthogonal reactions allowing both removal and linkage of chemical entities on complex biomolecules. We recently discovered a novel reaction between iminosydnones and strained alkynes leading to two products resulting from ligation and fragmentation of iminosydnones under physiological conditions. We now report the synthesis of a panel of substituted iminosydnones and the structure reactivity relationship between these compounds and strained alkyne partners. This study identified the most relevant substituents, which allow to increase the rate of the transformation and to develop a bifunctional cleavable linker with improved kinetics. Abstract : The chemistry of iminosydnones has been investigated and their reactivity to undergo click and release reactions with cyclooctynes has been evaluated. This structure reactivity relationship study conducted to the rational design of bioorthogonal cleavable linkers with improved kinetics and potential applications for chemical biology.